Moyamoya disease: Chronic headache and progressive dementia associated with multiple brain strokes - Castañeda, Marco A. (2019)
The case of a 32 years old. male patient who since age 17 has experienced constrictive headaches of several minutes’ duration, triggered by physical effort is reported. For the last seven years there, he has presented a progressive cognitive decline cognitive, and marked personality changes, having become extremely dependent even for conducting elemental activities. At the age of 27, he experienced total left hemiplegia from which he completely recovered in two weeks. He also shows severe confusional states and child-like behavior. Laboratory tests ruled out heart disease, atherosclerosis and systemic autoimmune diseases. Brain neuroimaging tests (CT, Angio – TEM and contrasted cerebral MRI) revealed the occurrence of six cerebral infarcts, in subacute and chronic stages, severe stenosis of the anterior cerebral arteries, and presence of microaneurysm in the M segment of the left middle brain artery. A limitation of this report is the absence of a study with digital angiography, due to economic difficulties. In short, the case of a patient with chronic headache associated with progressive dementia is presented, with neuroimaging and neuropsychological tests that support the diagnosis of of cognitive impairment associated with Moyamoya disease.